Do public health indicators affect life expectancy? - Kurniawan, Afif; Mamesah, Marline Merke; Wijaya, Hermanto; Putri, Linta Meyla (Jurnal Ilmu Kesehatan, 2024)
Indonesia has implemented a decentralization policy since the end of the Soeharto era. Decentralization gives central government tasks to local governments. Local governments are obliged to manage, develop regions, and improve the welfare of their people. Each region has its own policies in improving the health of its people. To monitor the achievement of the success of the health system in each region, a clear and broad picture is needed. One of them is the index. East Java is one of the provinces with the highest population in Indonesia. This study aims to see whether the indicators of Public Health Development in East Java have an influence on life expectancy. The results of the study showed that complete immunization and the proportion of doctors to residents in 1 sub-district have an influence on life expectancy. To improve immunization achievement, the government has launched various programs. The government is also carrying out equal placement of doctors through various health programs. The indicators measured are used as monitoring and evaluation materials for programs that have been carried out. Further research is needed regarding the relationship between regions and life expectancy.